Adherence to attendance at outpatient clinic, quality of prehospital therapy, and direct outcome of acute coronary syndrome: analysis within LIS-3 registry - Yu. V. Semenova; N. P. Kutishenko; A. V. Zagebelnyy; A. D. Deev; M. L. Ginzburg; S. Yu. Martsevich (Столичная издательская компания, 2016)
Aim. To assess the influence of patients' adherence to attendance at outpatient clinics (OPC) on direct outcome of acute coronary syndrome (ACS).Material and methods. Patients (n=320) hospitalized with ACS were divided into 3 groups depending on their attendance at OPC before ACS: group A - committed to attending OPC (n=139); group B - partially committed to attending OPC (n=103); group C - non-committed to attending OPC (n=78). Direct outcome of ACS and its connection to attendance at OPC was analyzed. The primary end point of the study was the development of myocardial infarction or unstable angina as direct outcome of ACS.Results. The majority of patients had myocardial infarction as direct outcome ofACS.Development of myocardial infarctionwas aboutthe same in3groups of attendance at OPC (p=0.158). Influence of patients' adherence to attendance at OPC on direct outcome of ACS was not found (RR=0.602, р=0.123). History of ischemic heart disease and myocardial infarction didn't change this predicted pattern. In the absence of significant influence of patients' adherence to attendance at OPC on the direct ACS outcome, it was decided to evaluate the effect of pre-hospital care quality on direct outcome of ACS, regardless of patients' adherence to attendance at OPC. Quality of pre-hospital therapy was low, but therapy of patients with unstable angina as an outcome of ACS was significantly better than therapy of patients with myocardial infarction as an outcome of ACS. Taking antiplatelet agents, beta-blockers and long-acting nitrates before ACS development significantly reduced the risk of myocardial infarction as an outcome of the ACS.Conclusion. Patients' adherence to attendance at OPC didn't influence direct outcome of ACS by itself, even considering the history of ischemic heart disease and myocardial infarction. Quality of pre-hospital therapy of patients with unstable angina as an outcome of ACS was significantly better than therapy of patients with myocardial infarction as an outcome of ACS. This is especially true in terms of drugs with proven effects on disease outcome. Taking antiplatelet agents, beta-blockers and long-acting nitrates before ACS development significantly reduces the risk of myocardial infarction as an outcome of the ACS